PHYSIOTHERAPY MANAGEMENT FOR CERVICAL ROOT SYNDROME: A CASE STUDY - Zaman, Alifia Fatimah; Wahyuni, W; Israwan, Wiek (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Cervical root syndrome (CRS) is a pain that extends from the vertebrae of the neck to the arms. The occurrence of CRS can be caused by factors related to activity, posture, and degenerative changes of the cervical discs that can be caused by age, trauma, repetitive movements, and work. The appearance of such pain can decrease productivity, quality of life, and social activities. Problems caused by cervical root syndrome are sharp spreading pain, muscle weakness, spasm in the cervical muscles, and a decrease in ROM to decrease the functional ability of the patient Case Presentation: The patient age 54 years old came to the Dempo clinic in Malang with a CT-Scan with the results of hernia nucleus pulposus in C3 and C4 and with complaints of pain radiating from the neck to the left arm since 2 weeks ago. Activities that aggravate complaints are when the patient looks up, turns to the left, when going to sleep, and when typing using a laptop for a long time. Pain will be reduced when sleeping at night. The patient is a lecturer whose activities are a lot of sitting, standing, and using a laptop to teach. Management and Outcome: Patient receive therapy three times in once a week. Ultrasound therapy and cervical traction were used for the patient. The Numeric Rating Scale (NRS), Range of Motion using metline, and Neck Disability Index (NDI) were used to evaluate patient. Discussion: After therapy in three weeks with ultrasound and cervical traction, the pain decreases and ROM increases. The functional ability of the neck decreased the disability rate from 26% to 20%. Conclusion: Physiotherapy program conducted in three times for three weeks’ therapy with physiotherapy modalities used such as ultrasound and mechanical traction is able to reduce pain and restore the body's function to carry out daily activities.